P149 Searching for bile acid malabsorption using serum fibroblast growth factor 19 (FGF19) and faecal bile acids in patients with inflammatory bowel diseases, microscopic colitis and irritable bowel syndrome. (25th January 2019) - Lyutakov, I; Nakov, R; Nakov, V; Vladimirov, B; Dimov, A; Asenova, B; Chetirska, M; Vatcheva-Dobrevska, R; Penchev, P
Abstract: Background: Excessive amounts of bile acids (BA) entering the colon due to bile acid malabsorption (BAM) cause chronic bile acid diarrhoea (BAD). Fibroblast growth factor 19 (FGF19) is the ileal hormone providing feedback inhibition of BAs synthesis in the liver. Little is known about the mechanisms of BA dysregulation in patients with inflammatory bowel disease (IBD), irritable bowel syndrome (IBS-D) and microscopic colitis (MC). Methods: The aim was to evaluate the diagnostic accuracy of serum levels of FGF19, total free faecal bile acids (TFFBA), and faecal calprotectin (FC) in patients with chronic diarrhoea. Methods: we enrolled 40 adult patients with chronic diarrhoea who underwent standard laboratory tests, colonoscopy, serum FGF19, FC, TFFBA. Patients were divided into five groups: 14 patients with active IBD, 5 patients with IBD in remission, 5 patients with IBD after surgery, 11 patients with IBS-D and 5 patients with MC. Fasting serum FGF19, TFFBA were measured by ELISA test and FC by the quantitative immunochromatographic method. Results: Diagnosis of BAM was confirmed in 24 of 40 patients (60%) and excluded in 16 of 40 patients (40%). For IBS-D, serum FGF19 produced a ROC curve with AUC of 0.777 ( p -value of 0.007 and 95% CI [0.628–0.927]). Sensitivity and specificity of FGF19 were 72.7% and 72.4%, respectively for a cut-off value of 88.22 pg/ml, which will lead to accurate prediction of BAM in 72% IBS-D patients. TFFBA shows no significant difference between all the groups. Conclusions: BAM is very under-diagnosed and FGF19 could be used for screening for BAM in patients with chronic diarrhoea, because there is bile acid binder's treatment. Further bigger studies are needed to establish the efficacy of FGF19 and TFFBA.